Spectroscopy of high angular momentum Rydberg states with 2S1/2 ion cores - Snow, Erica Lynn, author; Lundeen, Stephen R., advisor (Colorado State University. Libraries, 2006)
The fine structure intervals of n=17 and 20 have been measured in magnesium and barium for a range, 7≤L≤13, of angular momentum states. This systematic study used microwave spectroscopy with selective laser excitation for detection of Rydberg levels by Stark ionization. These precise measurements lead to up to two orders of magnitude improvement from past experimental determinations of the induced polarizabilities of the ground state ionic cores. The measured polarizabilities are, for Mg+, αd = 35.02(4)α30 and αQ = 202(54)a50, and for Ba+, αd = 124.09(27)a30 and αQ = 4238(643)a50. An opportunity to test the adequacy of the long-range model, historically used to treat high-angular momentum fine structure data, is possible with the availability of independent theoretical calculations. Previously, studies have revealed excellent agreement with calculated values of the induced dipole polarizability of the ion core. A large discrepancy is found, however, between experiment and the best theoretical calculations for the induced quadrupole polarizability. These previous disagreements between theory and experiment for 2S1/2 systems have been largely resolved in this work. In addition, the inclusion of core fine structure in the long-range model will be shown to describe the spin-orbit splittings of high-L barium states.
Keywords: optics; atomic physics